PANDANREJO TOURISM VILLAGE DIGITAL BRANDING IDENTITY ANALYSIS - Dendy Sundayana; Linandar Tanuwijaya; Mohamad Ridwan; Darmawan Sundayana; Odang Rusmana (Politeknik Pariwisata NHI Bandung, 2024)
Tourism is one of the factors affected by the COVID-19 pandemic, but after the COVID-19 pandemic, tourism began to rise. There was the phenomenon of